2019
DOI: 10.1016/j.postharvbio.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pathogenicity-related genes and the role of a subtilisin-related peptidase S8 (PePRT) in authophagy and virulence of Penicillium expansum on apples

Abstract: Blue mold caused by Penicillium expansum is a major postharvest disease of pome fruit. Several mechanisms possibly involved in P. expansum pathogenicity and virulence. However, factors that mediate pathogenicity and virulence are largely not yet characterized. In this work we analyzed P. expansum predicted secretome to reveal potential genes that have a role in host-pathogen interaction. A prediction pipeline was designed using an approach that combines common effector features, transcriptomic data and homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 77 publications
1
28
0
Order By: Relevance
“…The host responded by activating pathogen-associated molecular pattern (PAMP)-triggered immunity (PTI) one hour after infection, and effector-triggered immunity three hours after infection. In another gene expression study of P. expansum, genes coding for pectin degradation were again shown to be upregulated during infection of apple [ 79 ]. Barad et al [ 32 ] showed that gene expression patterns of P. expansum are, however, extremely versatile; some genes expressed during infection of apple were pH neutral, while others were similar to those obtained when growing the fungus in vitro at pH 4 or at pH 7, respectively.…”
Section: Resistance Mechanisms and Quest For Resistance Genesmentioning
confidence: 99%
“…The host responded by activating pathogen-associated molecular pattern (PAMP)-triggered immunity (PTI) one hour after infection, and effector-triggered immunity three hours after infection. In another gene expression study of P. expansum, genes coding for pectin degradation were again shown to be upregulated during infection of apple [ 79 ]. Barad et al [ 32 ] showed that gene expression patterns of P. expansum are, however, extremely versatile; some genes expressed during infection of apple were pH neutral, while others were similar to those obtained when growing the fungus in vitro at pH 4 or at pH 7, respectively.…”
Section: Resistance Mechanisms and Quest For Resistance Genesmentioning
confidence: 99%
“…There are >80 proteases in the secretome of P. expansum, and about half of them belong to a superfamily of serine proteases (Li et al, 2015). Levin, Kishore et al (2019) reported that Peprt, a gene encod-ing a protein in the S8 family of serine proteases in P. expansum, was upregulated after 24 hr of inoculation. The deletion of Peprt resulted in reduced P. expansum virulence on apple fruit.…”
Section: Secreted Proteasesmentioning
confidence: 99%
“…In recent years, there have been rapid increases in research on the molecular mechanisms of pathogenicity in P. expansum , especially after the sequencing of the genomes of P. expansum and closely related Penicillium species. A large set of genes coding putative virulence factors and regulators have been identified in several omics‐based studies (Ballester et al., 2015; Levin, Kishore et al., 2019; Tannous, Kumar et al., 2018; Wang, Zheng, Zhang et al., 2019; Wu et al., 2019; Zhou et al., 2018), and the functions of some genes have been characterized (Figure 2).…”
Section: Molecular Mechanisms Of Pathogenicity In P Expansummentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous works [11,12], the potential role of PeLysM and subtilisin-related peptidase Peprt genes in the pathogenicity and virulence of P. expansum on apples was investigated. Deletion of Peprt in P. expansum resulted in reduced sporulation and virulence of the fungus on apples [12]. Expression level of four LysM coding genes was induced during the infection of apple fruit and decay development.…”
Section: Introductionmentioning
confidence: 99%